Unreal Engine VR Cookbook : developing virtual reality with UE4 - McCaffrey, Mitch, ....- (Boston : Addison-Wesley, 2017)
For game developers and visualization specialists, VR is the next amazing frontier to conquer—and Unreal Engine 4 is the ideal platform to conquer it with. Unreal ® Engine VR Cookbook is your complete, authoritative guide to building stunning experiences on any Unreal Engine 4-compatible VR hardware. Renowned VR developer and instructor Mitch McCaffrey brings together best practices, common interaction paradigms, specific guidance on implementing these paradigms in Unreal Engine, and practical guidance on choosing the right approaches for your project. McCaffrey's tested “recipes” contain step-by-step instructions, while empowering you with concise explanations of the underlying theory and math. Whether you're creating first-person shooters or relaxation simulators, the techniques McCaffrey explains help you get immediate results, as you gain “big picture” knowledge and master nuances that will help you succeed with any genre or project. •Understand basic VR concepts and terminology •Implement VR logic with Blueprint visual scripting •Create basic VR projects with Oculus Rift, HTC Vive, Gear VR, Google VR, PSVR, and other environments •Recognize and manage differences between seated and standing VR experiences •Set up trace interactions and teleportation •Work with UMG and 2D UIs •Implement character inverse kinematics (IK) for head and hands •Define effective motion controller interaction •Help users avoid motion sickness •Optimize VR applications •Explore the VR editor, community resources, and more If you're ready to master VR on Unreal Engine 4, this is the practical resource you've been searching for!
Keywords: Virtual Reality